Relationship is Everything: Holistic Approaches to Aboriginal Child and Youth Mental Health - Carriere, Jeannine; Richardson, Cathy (First Peoples Child & Family Review, 2013)
This article addresses topics related to Indigenous holistic well-being including, 1) Indigenous perspectives on Aboriginal child and youth holistic mental health; 2) Factors undermining Indigenous well-being; 3) Process and curriculum for training to support mental health practitioners working with Indigenous children, youth and communities; 4) concrete applications and participant feedback. To begin, it is important to explore the following question: What is holistic mental health for First Nations, Métis and Inuit children and youth? In outlining this training curriculum we hope to contribute to a broader conversation about supporting and enhancing the well-being of Indigenous children and youth in Canada.